2015
DOI: 10.1515/cppm-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Diglycolamide-Based Solvent Systems in Room Temperature Ionic Liquids for Actinide Ion Extraction: A Review

Abstract: This review article gives a comprehensive account of the extraction of actinide ions using room temperature ionic liquid-based solvent systems containing diglycolamide (DGA) or functionalized DGA extractants. These extractants include multiple DGA-functionalized ligands such as tripodal DGA (T-DGA) and DGA-functionalized calix [4]arenes (C4DGA). Apart from metal ion extraction behaviour, other important features of the ionic liquid-based solvent systems such as separation behaviour, luminescence spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…This plot (given as Supporting Information Figure S6) results in two different straight lines having different slopes, thereby indicating two different extraction mechanisms of UO 2 2+ by TSIL in [Me 3 NBu]­[NTf 2 ] phase at higher and lower HNO 3 concentrations. At higher acidity (1.0–5.0 mol L –1 ) the extraction occurs via solvation or ion-pair mechanism, whereas at lower acidity ((0.1–1) × 10 –6 mol L –1 ) it follows a cation-exchange mechanism. , However, in lower acidity a plateau was observed below 1 × 10 –4 mol L –1 HNO 3 concentration, which is a typical behavior of cation-exchange extraction mechanism. In order to confirm the complexation mechanism of TSIL with UO 2 2+ ion, studies were carried out at lower (0.01 mol L –1 ) and higher (2.0 mol L –1 ) HNO 3 concentration using isothermal calorimetric titration (ICT).…”
Section: Resultsmentioning
confidence: 97%
“…This plot (given as Supporting Information Figure S6) results in two different straight lines having different slopes, thereby indicating two different extraction mechanisms of UO 2 2+ by TSIL in [Me 3 NBu]­[NTf 2 ] phase at higher and lower HNO 3 concentrations. At higher acidity (1.0–5.0 mol L –1 ) the extraction occurs via solvation or ion-pair mechanism, whereas at lower acidity ((0.1–1) × 10 –6 mol L –1 ) it follows a cation-exchange mechanism. , However, in lower acidity a plateau was observed below 1 × 10 –4 mol L –1 HNO 3 concentration, which is a typical behavior of cation-exchange extraction mechanism. In order to confirm the complexation mechanism of TSIL with UO 2 2+ ion, studies were carried out at lower (0.01 mol L –1 ) and higher (2.0 mol L –1 ) HNO 3 concentration using isothermal calorimetric titration (ICT).…”
Section: Resultsmentioning
confidence: 97%
“…Diglycolamides (DGAs), with their tridentate O-donating ligands, have the ability to form stable complexes with lanthanides and actinides. Therefore, diglycolamide-based systems in IL have been investigated for the recovery of such metals [139]. It was found that N,N,N ,N -tetraoctyl diglycolamide (TODGA) allows the enhancement of the extraction performance for REEs when it is diluted in [C 1 C 4 im] [NTf 2 ] in comparison to an isooctane system.…”
Section: Neutral Extractantsmentioning
confidence: 99%
“…On the other hand, without addition of a hydrophobic cationic exchanger, dissolving the extractant into the ionic liquid can also result in a high extraction efficiency for lanthanides, still based on the cation-exchange mechanism. 58,59 Diglycolamide-functionalized specific ionic liquids with functional groups attached to the cationic part of the ionic liquid showed high extraction efficiency to actinides and lanthanides. [59][60][61] Verboom and co-workers also reported on a series of new ligands based on diglycolamides that have three functional groups at C-pivot and trialkylphenyl platforms.…”
Section: Extractants Based On Diglycoamidesmentioning
confidence: 99%
“…58,59 Diglycolamide-functionalized specific ionic liquids with functional groups attached to the cationic part of the ionic liquid showed high extraction efficiency to actinides and lanthanides. [59][60][61] Verboom and co-workers also reported on a series of new ligands based on diglycolamides that have three functional groups at C-pivot and trialkylphenyl platforms. 62 These ligands also showed high affinity for Am(III) and Eu(III) with a 1 : 1 metal to ligand stoichiometry.…”
Section: Extractants Based On Diglycoamidesmentioning
confidence: 99%